FORECASTING THE VALUE AND THE PRICE/EARNINGS RATIO OF THE INDUSTRIAL COMPANY WITH THE CONSTANT ANNUAL GROWTH OF ITS EARNINGS - Zemlyanskiy, Oleg; Mazurina, Tatyana; Neopulo, Klavdiya; Kuksov, Alexandr (Revista Inclusiones, 2019)
The growth of the company’s value and the value of the monetary unit of its earnings depends on the growth of the company’s earnings, and this interdependence is explored in this article. A method for calculating and analyzing the company’s value and its Price/Earnings (P/E) ratio at a forecasted cash flow with a constant increase in the company’s earnings over a certain number of periods (years) is proposed. An analysis of the value and dynamics of the company’s P/E ratio is provided for the different but constant company’s earnings growth over a given period, based on the company’s value growth ratio formula or the company’s P/E ratio and the company’s constant annual earnings growth over several periods. The proposed formula and method for calculating the P/E ratio of a company with a forecasted cash flow and a constant annual growth of the company’s earnings over several periods allow estimating its value and the P/E ratio for various values of the company’s annual earnings growth over several periods, forecasting the company’s position in the stock market, comparing it with the position of competing companies, comparing the dynamics of growth in the value and earnings of the company, and estimating the required annual earnings growth or the number of periods (years) required for maintaining a certain earnings growth for the company to occupy the desired position in the stock market.